PENGARUH ELECTRONIC WORD OF MOUTH DAN BRAND IMAGE TERHADAP MINAT BELI CARASUN - Ni Putu Anjelina Dewi (Jurnal Performa)
People are aware of the importance of taking care of the body by using cosmetic products. Cosmetic is medicine  or ingredient to be able to beautify the body in which  the treatment can be in the form of bodycare, haircare, skincare. According to Switzerland Global Enterprise (Mitel Market Research Institute, Statista, Independent) stated that Indonesia will be in the top five ranked in the world's largest cosmetic market within 10-15 years which are estimated the percentage of 7,2%  and high demand of  the society. With the advancement of technology in which has to face competitors, therefore the company has to improve the quality and quantity of product marketing in order to compete with other companies. The purpose of this research is to find out the influence of electronic word of mouth and brand image on Carasun beauty products. Therefore, the author wants to do research with the influence of electronic word of mouth and brand image on the purchase intention of Carasun beauty products. To collect data in this research, the  researcher distributes questionnaires to 110 respondents with the criteria of  people who know Carasun products, domicile in Surabaya, uses Instagram, the age of 17 to 26 years old . The method that is used in this research is purposive sampling method and statistics with the help of  SPSS program. This research uses quantitative research method. The analysis method that is used in this research is  validity test, reliability test, classical assumption test, multiple linear regression analysis, F test, t test, determination coefficient test, and correlation coefficient. The result of this research  indicates that the electronic word of mouth variable affects on purchase intention and brand image variable affects on purchase intention.